Multi-scenario simulation of land use dynamics and ecological risk: a case study of the liaohe estuary national wetland reserve using PLUS-Markov and PSR models - Hu, Nanlin; Wang, Guodong; Ma, Zijun; Zhao, Meiling; Yuan, Yusong; Zhang, Tao; Chen, Qi; Meng, Jingci; Wang, Jiaying (Frontiers in Environmental Science, 2024)
Introduction: Wetland has been exposed to tremendous stresses and hazards, leading to many potential ecological risks in the past few decades. There is an urgent need to assess the ecological risk status of the wetland, especially when examining how the intensity of socio-economic growth, policy changes, and other variables affect land use and ecological risk changes. Methods: This study models the LULC pattern in the Liaohe Estuary National Nature Wetland Reserve under various future scenarios in 2000–2040 and develops a long-term Pressure-State-Response ecological risk assessment model based on the characteristics of the northern wetland environment in China, combined with the simulated multi-scenario PLUS model. Results: As the two most distinct vegetation types in the reserve area, Phragmites australis and Suaeda glauca presented decreasing trends of 59.7 ha/year and 9.0 ha/year in the economy development scenario (EDS), higher than 57.3 ha/year, 8.2 ha/year in the natural increase scenario (NIS), and 35.4 ha/year and 5.8 ha/year in the ecological protect scenario (EPS). From the core area to the buffer area to the outer experimental area, the slope rate of vegetation deterioration rises severely. In comparison to the scenario of EDS, the area of aquiculture and oil wells can be lowered by 11.4 ha/year and 1.1 ha/year with the application of ecological protection measures. Besides, under three scenarios, mean ecological risks are all showing an increasing trend from 2000 to 2040, which is generally higher in the EDS scenario than that in the NIS and EPS scenarios. The proportion of the high and very high level of ecological risk area continually increased from 28.8% to 40.4% from 2000 to 2040, which was mainly located in the south estuary and west urban areas. In addition, among the three protected areas, the ecological risk in the core area has a lower growth rate than that in the outer buffer zone and experimental zone. Discussion: Aiming for the development of Liaohe Estuary National Park, these findings provide quantitative guidance for protecting and restoring natural resources.